2017
DOI: 10.4236/wjet.2017.52025
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Prototype of a Novel Intramedullary Injectable Bioresorbable Polymer-Bioresorbable Balloon Osteosynthesis and a Volar Locking Plate for Treatment of Distal Radius Fractures

Abstract: Background: There is a large assortment of modalities for the surgical treatment/management of distal radius fractures (DRFs), where the most widely used is the fixed-angle volar plating (VLP) system, which, sometimes, is referred to as the "surgical modality of choice". While outcomes with each modality are usually good to excellent, each has its share of shortcomings and complications. Thus, there is scope for improvements to existing modalities and/or introduction of new ones. Study Purpose: We introduce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 36 publications
0
8
2
Order By: Relevance
“…Furthermore, the stiffnesses of the FIXATOR CONSTRUCT Model cases are within the range of values reported in the aforementioned literature studies (see Table A1 in Appendix). It is also worth pointing out that the present FEA results buttress those obtained in our experimental biomechanical study of these two constructs [11].…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Furthermore, the stiffnesses of the FIXATOR CONSTRUCT Model cases are within the range of values reported in the aforementioned literature studies (see Table A1 in Appendix). It is also worth pointing out that the present FEA results buttress those obtained in our experimental biomechanical study of these two constructs [11].…”
Section: Discussioncontrasting
confidence: 51%
“…In brief, it is envisaged that using the fixator would involve creating an entry portal into the fractured bone, using a flexible cannulated drill to prepare the intramedullary canal, inserting a compliant balloon catheter into the bone, reducing the fracture, injecting a bioresorbable polymer into the balloon, expanding the balloon to fully conform to the shape of the canal, and allowing the polymer to cure. In that study, we found that each of the determined biomechanical parameters of a construct that included the fixator was comparable to that when fixation was with a commercially-available volar locking plate [11].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…To avoid high variabilities in geometry and material properties, as well as to accommodate the special handling requirements of cadaver radii, the synthetic radius was designed to simulate structural and material properties of cadaveric radius, while providing the low variabilities in geometry and material properties, as well as fulfilling the simple handling requirements. Synthetic radii have frequently been used for the biomechanical tests of treated DRFs [ 8 , 9 , 10 ]. Although the variabilities in geometry and material properties of synthetic radii can be controlled, the high deviations of stiffness are surprisingly observed in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…During biomechanical tests, pure compression without any bending and/or shear is expected. It is speculated that the high deviations of stiffness [ 8 , 9 , 10 ] may relate to the inconsistency of applied mechanical actions (i.e., the tested synthetic radii may be under the various combinations between compression, bending, and shear). In the present study, a biomechanical apparatus and an experimental procedure were proposed for the biomechanical tests of radii under pure compression.…”
Section: Introductionmentioning
confidence: 99%